Critical Analysis of Nursing Approaches to Modern Healthcare Challenges - Al-Harbi, Rehab Saad; Alanazi, Yasmeen Hussain; Alanizi, Dalal Ayat; Alanazi, Khulud Ayyat; Alanazi, Amal Ali; Almutairi, Enthar Ayadh; Alanazi, Ashwaq Lafi; Alosimi, Alnearah Abduallh; Alruwaili, Karimaha Mukhlef; Alruwaili, Anwar Mukhilf (Journal of Ecohumanism, 2024)
In today's fast-evolving framework of the healthcare systems, nursing is a key fundamental factor in healthcare delivery and enhancements of patients' positive experiences. However, the nursing profession has several issues, including rising demand for the number of patients, advanced technology, a lack of nurses, and a growing population. With this background, this critical analysis seeks to assess the strategies adopted in nursing about these contemporary healthcare challenges, especially with emphasis on the status of the role of nurses, technological advancement, and competent workforce development. The current review also reviews existing literature, establishes important areas of concern, and makes fact-based suggestions that help enhance practice among nurses. The infusion of new technologies, espousing constant professional development and more effective collaboration, can assist in the evolving nature of the nursing profession, which in turn will help to augment the delivery of care and the quality of associated patient outcomes.